2014
DOI: 10.1371/journal.pone.0101062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Reduced Nerve Toxicity by Titanium Dioxide Nanoparticles in the Phoxim-Exposed Brain of Bombyx mori

Abstract: Bombyx mori (B. mori), silkworm, is one of the most important economic insects in the world, while phoxim, an organophosphorus (OP) pesticide, impact its economic benefits seriously. Phoxim exposure can damage the brain, fatbody, midgut and haemolymph of B. mori. However the metabolism of proteins and carbohydrates in phoxim-exposed B. mori can be improved by Titanium dioxide nanoparticles (TiO2 NPs). In this study, we explored whether TiO2 NPs treatment can reduce the phoxim-induced brain damage of the 5th la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Previously, we demonstrated that citrate-coated AgNPs plays an important role in energy metabolism as evidenced by a balance between aerobic to anaerobic marker enzymes succinate dehydrogenase and lactate dehydrogenase, respectively in AH infected fishes (8). Further, titanium dioxide nanoparticles protect silkworm, Bombyx mori against phoxim induced oxidative stress and neurotoxicity (24,25). Thus, it seems obvious that response of biological systems towards different combinations of NPs differ at the perspective of toxicological aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that citrate-coated AgNPs plays an important role in energy metabolism as evidenced by a balance between aerobic to anaerobic marker enzymes succinate dehydrogenase and lactate dehydrogenase, respectively in AH infected fishes (8). Further, titanium dioxide nanoparticles protect silkworm, Bombyx mori against phoxim induced oxidative stress and neurotoxicity (24,25). Thus, it seems obvious that response of biological systems towards different combinations of NPs differ at the perspective of toxicological aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies of Xie et al and Su et al (24,25) reported that Titanium dioxide nanoparticles (TiO 2 NPs) protected brain tissue from oxidative stress induced by organophosphorus pesticide, phoxim in silk worm, Bombyx mori. The same authors indicated that TiO 2 NPs suppressed oxidative stress in selected tissues of insects might be due to regulation of expression of genes such as caspases which are believed to be important in oxidative stress and mitochondria and respiratory chain (24,25). Recently, studies of Oliveira et al (34), indicated that AgNPs with organic additives such as (1) 5-Aminoisoquinoline, (2) 7-amino-4-methylcoumarin, and (3) 2-Aminoanthraceneas did not elicit same responses in pro-(malondialdehyde levels) and antioxidant enzymes such as CAT and GST in intestine and liver tissues of gold fish, Carassius auratus.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Therefore, the lack of change in the oxidative stress parameters observed here was reasonable and consistent with a previous study. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment by TiO 2 NPs increased antioxidant capacity and acetylcholinesterase (AChE) activity in intoxicated silkworm and improved B. mori larval survival under phoxim-induced toxicity [199]. TiO 2 NPs pre-treatment also reduced the phoxim-induced brain damage of the 5th larval instar of B. mori; under phoxim exposure they relieved severe brain damage and oxidative stress in the brain and inhibited the down-regulated expression of H + -transporting ATP synthase and vacuolar ATP synthase that are involved in ion transport and energy metabolism [200]. Moreover, TiO 2 NPs significantly decreased reduction of protein, glucose and pyruvate contents, lactate dehydrogenase, succinate dehydrogenase and malate dehydrogenase activities and attenuated increases of free amino acids, urea, uric acid and lactate levels, activities of protease, alanine aminotransferase and aspartate aminotransferase in the hemolymph of silkworms caused by phoxim exposure [201].…”
Section: Nanoinsecticidesmentioning
confidence: 99%